The impact of foreign investment on the liquidity of financial markets: Applied Study in the Iraqi Stock Exchange for the period (2005-2016) - Younis Al-Mousawi, Haydar; Saleh Al-Halawi, Ayat (Iraqi Journal for Administrative Sciences, 2024)
Foreign investment (both direct and indirect) has a very important impact on the global economy. The current study examined the implications of FDI inflows in the liquidity of financial markets and launched research to study the Iraqi market for securities. Capital systems, and foreign direct investment plays a prominent role in the economic development of all countries, especially developing countries that lack capital and low saving rates. The Iraqi financial market is the sample of the study from the financial markets attractive to foreign direct investment because of its multiple investment opportunities. Therefore, the possibility of exposure to the volatility resulting from indirect foreign investment decisions to enter the Iraqi financial market, so it is important to know the flow of foreign direct investment on the liquidity of the financial market by activating the indicators of the Iraqi market for securities, and analysis of some of the indicators relied on, Volume index and the number of shares traded. Therefore, the problem of research came despite the great importance of foreign direct investment, but Iraq after more than 16 years of economic and political change witnessed by Iraq after the events of 2003 is still suffering from the lack of investment opportunities in the field and delayed foreign direct investment, and then reflected This vision in the attraction of foreign direct investment inflow on the stock market in Iraq. The study sought to achieve several objectives, the most important of which is the statement of the nature and importance of foreign direct investment in the economy, as well as the knowledge of measuring the correlation between foreign direct investment and liquidity of the financial market and measuring the flow of foreign direct investment in the liquidity of the financial market. Based on the objective and the problem of research, the implications of the FDI inflow as an independent variable and its effect on the adopted variables, namely the volume of trading and the number of shares traded, were studied.